2017
DOI: 10.1016/j.stemcr.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human Induced Pluripotent or Embryonic Stem Cells Decreases the DNA Damage Repair by Homologous Recombination

Abstract: SummaryThe nitric oxide (NO)-cyclic GMP pathway contributes to human stem cell differentiation, but NO free radical production can also damage DNA, necessitating a robust DNA damage response (DDR) to ensure cell survival. How the DDR is affected by differentiation is unclear. Differentiation of stem cells, either inducible pluripotent or embryonic derived, increased residual DNA damage as determined by γ-H2AX and 53BP1 foci, with increased S-phase-specific chromosomal aberration after exposure to DNA-damaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…When DSBs are introduced, embryonic stem cells (ESCs) predominantly adopt high delity HRR to repair the lesions rather than NHEJ [24][25][26][27][28].However, when ES cells differentiate into somatic cells, the expression of HRR-related enzymes is down-regulated, whereas the expression of NHEJ-related enzymes, such as DNA Ligase IV, is up-regulated. As a result, DSB repair pathway shifts from HRR to NHEJ [26,29]. Consistently, the expression level of DNA Ligase IV during reprogramming displayed a signi cant downregulation after KMOS mRNAs transfection (Fig.…”
Section: Antioxidants Reduced Chromosomal Aberrations During Reprograsupporting
confidence: 67%
See 1 more Smart Citation
“…When DSBs are introduced, embryonic stem cells (ESCs) predominantly adopt high delity HRR to repair the lesions rather than NHEJ [24][25][26][27][28].However, when ES cells differentiate into somatic cells, the expression of HRR-related enzymes is down-regulated, whereas the expression of NHEJ-related enzymes, such as DNA Ligase IV, is up-regulated. As a result, DSB repair pathway shifts from HRR to NHEJ [26,29]. Consistently, the expression level of DNA Ligase IV during reprogramming displayed a signi cant downregulation after KMOS mRNAs transfection (Fig.…”
Section: Antioxidants Reduced Chromosomal Aberrations During Reprograsupporting
confidence: 67%
“…6e, f). In contrast, the expression levels of the HRR pathway-related proteins Rad51 and Rad52 increased gradually [29], reaching a peak on day 7 ( Fig. 6g-j).…”
Section: Antioxidants Reduced Chromosomal Aberrations During Reprogramentioning
confidence: 94%
“…Some studies have also shown that, compared with neural SCs, terminally differentiated descendant astrocytes lack functional DDR signaling. Mature astrocytes and dopaminergic neurons exhibit significantly higher residual damage, in comparison with their undifferentiated and neuronal progenitor cells, as demonstrated by the delayed disappearance of γ-H2AX foci 8–12 hr post irradiation [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was not observed in DNA repairedeficient xrs5 cells (Ku80-deficient), which indicated that DMSO at a lower concentration facilitated DNA DSB repair rather than suppressing the indirect action of irradiation (26). Recently, several studies reported that adult stem cells, such as cycling crypt base columnar cells, are relatively radioresistant, repairing DNA by homologous recombination significantly more efficiently than transitamplifying progenitors, and DNA damage repair by homologous recombination decreases along with the differentiation of human-induced pluripotent or embryonic stem cells (27)(28)(29). By analyzing phosphorylated H2AX (another marker of DNA DSBs), we found that DMSO treatment on local irradiated mice significantly decreased the average levels of g-H2AX foci in p63-positive lingual epithelial stem cells at 6 hours but not at 2 hours after irradiation.…”
Section: Discussionmentioning
confidence: 99%